Performance Appraisal System of Public Technical Universities of Malaysia- A Study - S. , Panda; M. , Waris; M. , Yusri; A.Q. , Adeleke; W.M.N. , Sarbani (International Journal of Psychosocial Rehabilitation, 2020)
Appraisal of employee performance is vital for technical universities. The Performance Appraisal System (PAS) is useful for periodical evaluation of job performance. Different factors are attributing to Performance Appraisal System of such universities. Factors like importance of PAS, Appraisal Process, Performance Planning, Documentation, Feedback, Reward and Performance Standards have significant impact on PAS. It is statistically evidence of perceptual variation about Performance Appraisal System among the respondents. More awareness and understanding of the importance of appraisal system shall be helpful for employees as well as the technical universities of Malaysia. Firstly, the essentiality of Performance Appraisal System for Technical Universities has been discussed in introduction. The literature pertaining to appraisal system is being reviewed in second part. Thirdly, methodology followed in this study has been mentioned. Fourthly, results and their analysis are discussed. Finally, concluding aspect of this article has been reflected.